Psychological effects of psychedelics in adolescents - Izmi, Nadhrah; Carhart-Harris, Robin Lester; Kettner, Hannes (Frontiers in Child and Adolescent Psychiatry, 2024)
This study aimed to investigate differences in long-term psychological effects, acute subjective effects, and side effects associated with psychedelic use in adolescents (aged 16-24), compared with adults (aged 25+). Data from two observational online survey cohorts was pooled, involving adolescents (average age 20.4 ± 2.2, N=435) and adults (average age 36.5 ± 9.7, range = 25-71, N=654) who self-initiated a psychedelic experience and were tracked via online surveys from a pre-experience baseline to four weeks post-use. Self-reported measures of well-being were collected one week before, and two and four weeks after psychedelic use. Acute subjective drug effects, dosage and contextual variables pertaining to the setting of use were measured on the day after the session. Repeated-measures analyses of covariance, t-and z-tests, as well as exploratory correlational and regression analyses tested differences in psychological changes, acute drug effects, and side effects between the two groups. Psychological well-being significantly improved in adolescents two and four weeks following psychedelic use, with a clinically relevant mean change score of 3.3 points (95% CI: 1.1 -5.5). on the Warwick-Edinburgh Mental Wellbeing Scale [F(1.8, 172.9)=13.41, η 2 G=.04, p<.001], statistically indistinguishable from changes in adults. Acute subjective effects differed between the age groups; adolescents reported significantly higher challenging experiences and ego-dissolution. In adolescents, visual symptoms related to 'hallucinogen persisting perceptual disorder' (HPPD) were reported at a higher prevalence than in adults (73.5 % vs 34.2 %, p<.001) but were reported as distressing by only one adolescent participant. To our knowledge, this is the first prospective study to examine the psychological effects of psychedelic use specifically in adolescents. Statistically significant improvements in psychological well-being and other domains of mental health were observed, consistent with effects seen previously in adults, providing tentative evidence for the potential utility of psychedelic interventions in adolescents. However, differences in acute subjective effects, specifically the less positive role of ego-dissolution experiences for long-term changes in adolescents, as well as a higher prevalence of HPPD-related symptoms suggest that special considerations might be required when assessing psychedelic treatment design and risks.